Proteomic analysis of the phycobiliprotein antenna of the cryptophyte alga Guillardia theta cultured under different light intensities - Kieselbach, Thomas (Photosynth Res, 2017)
Plants and algae have developed various light-harvesting mechanisms for optimal delivery of excitation energy to the photosystems. Cryptophyte algae have evolved a novel soluble light-harvesting antenna utilizing phycobilin pigments to complement the membrane-intrinsic Chl a/c-binding LHC antenna. This new antenna consists of the plastid-encoded β-subunit, a relic of the ancestral phycobilisome, and a novel nuclear-encoded α-subunit unique to cryptophytes. Together, these proteins form the active α(1)β·α(2)β-tetramer. In all cryptophyte algae investigated so far, the α-subunits have duplicated and diversified into a large gene family. Although there is transcriptional evidence for expression of all these genes, the X-ray structures determined to date suggest that only two of the α-subunit genes might be significantly expressed at the protein level. Using proteomics, we show that in phycoerythrin 545 (PE545) of Guillardia theta, the only cryptophyte with a sequenced genome, all 20 α-subunits are expressed when the algae grow under white light. The expression level of each protein depends on the intensity of the growth light, but there is no evidence for a specific light-dependent regulation of individual members of the α-subunit family under the growth conditions applied. GtcpeA10 seems to be a special member of the α-subunit family, because it consists of two similar N- and C-terminal domains, which likely are the result of a partial tandem gene duplication. The proteomics data of this study have been deposited to the ProteomeXchange Consortium and have the dataset identifiers PXD006301 and 10.6019/PXD006301.